Tęsknota za ideałem. Rola dzieci w filmach i filozofii twórczej Andrieja Tarkowskiego - Sławnikowski , Wojciech (Przestrzenie Teorii, 2020)
The topic of the article is the role of child characters in Andrei Tarkovsky’s oeuvre. The first part concerns the early films in which children appear as main characters and represent a spiritual ideal. In the second part, later films are analysed in terms of the presence of adult characters striving for this ideal.